Microstructural Investigation and Wear Characteristics of Al-Si-Ti Cast Alloys - SUBHI, Akeel Dhahir; KHLEIF, Ali Abbar; ABDUL-WAHID, Qasim Saad (Engineering Transactions, 2020)
Hypoeutectic Al-7Si alloys containing various titanium proportions (0.8–1.6%) were produced and analyzed in this work. The wear characteristics of Al-Si alloys were studied under the conditions of dry sliding at various applied loads. Optical microscope (OM), scanning electron microscopy (SEM) and X-ray diffraction (XRD) were used to depict the microstructure, worn surface and phases, respectively. Phases of α-Al, eutectic and Ti9Al23 were recognized in the Al-Si-Ti alloys matrix. Considerable coarsening took place in α-Al and eutectic silicon in a fully eutectic through solidification. The hardness was increased as the titanium proportion increased. Furthermore, significant changes were found in the wear rate depending on thetitanium proportion added and load applied.